2006
DOI: 10.1158/0008-5472.can-06-1213
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Identify Epithelial-to-Mesenchymal Transition and Activation of Nuclear Factor-κB Signaling as Characteristics of a High-risk Head and Neck Squamous Cell Carcinoma

Abstract: Gene expression signatures generated from DNA microarray analyses have shown promise as predictive biomarkers of clinical outcome. In this study, we determined a high-risk signature for disease recurrence using formalin-fixed head and neck squamous cell carcinoma (HNSCC) tumors and compared the results with an independent data set obtained from fresh frozen tumors. We also showed that genes involved in epithelial-to-mesenchymal transition (EMT) and nuclear factor-KB (NF-KB) signaling deregulation are the most … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
150
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(170 citation statements)
references
References 38 publications
16
150
2
2
Order By: Relevance
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of statistical techniques to control for RNA degradation and block age, it may be possible to glean useful information from hybridizations that we considered uninformative. For example, Chung et al 31 have recently reported a statistical approach to account for block age of FFPE samples. Also, supervised analysis 32 with respect to a variable of clinical interest (eg patient outcome) may minimize the effect of certain systematic biases across the data set.…”
Section: Discussionmentioning
confidence: 99%
“…The same gene list was used by Chung et al (2006) to describe activation of NF-kB in high-risk head and neck squamous cell carcinoma. The NF-kB signature was mapped onto our informative gene list resulting in 93 common genes between the NF-kB signature and our informative gene list.…”
Section: Discussionmentioning
confidence: 99%